Clomiphene Stair-Step Protocol for Women With Polycystic Ovary Syndrome. Issue 1 (January 2018) - Jones, Tiffanny; Ho, Jacqueline R.; Gualtieri, Marc; Bruno-Gaston, Janet; Chung, Karine; Paulson, Richard J.; Bendikson, Kristin A.
Abstract : OBJECTIVE: To compare time to ovulation, ovulation rates, and side effect profile of traditional and the stair-step protocol for ovulation induction using clomiphene citrate in women with polycystic ovary syndrome (PCOS). METHODS: We performed a retrospective study of women seeking care for infertility with a diagnosis of PCOS at a university-based infertility clinic from July 2012 to July 2014. We included patients who were resistant to the initial starting dose of 50 mg clomiphene. The primary outcome was time to ovulation. Secondary outcomes included ovulation rates, clinical pregnancy rates, and mild and moderate-to-severe side effects based on dose. For the traditional protocol, higher doses of clomiphene were used each subsequent month if no ovulation occurred. For the stair-step protocol, higher doses of clomiphene were given 7 days after the last dose if no dominant follicles were seen on ultrasonography. Our study had 80% power to detect a 20% difference in ovulation. RESULTS: One hundred nine patients were included in the analysis with 66 (60.6%) in the traditional and 43 (39.4%) in the stair-step protocol. Age and body mass index were similar between groups. The time to ovulation was decreased in the stair-step protocol group compared with the traditional protocol group (23.1±0.9 days vs 47.5±6.3 days). Ovulation rates were increased in the stair-step group compared with the traditional group at 150 mg (16 [37%] vs 8 [12%], P =.004) and at 200 mg (9 [21%] vs 3 [5%], P =.01). Pregnancy rates were similar between groups once ovulation was achieved (12 [18.1%] vs 7 [16.3%], P =.08). The stair-step protocol had an increased incidence of mild side effects (vasomotor flushes, headaches, gastrointestinal disturbance, mastalgia, changes in mood; 18 [41%] vs 8 [12%]), but there was no difference in the incidence of severe side effects (headaches, visual disturbances). CONCLUSION: For women with PCOS, the stair-step clomiphene protocol is associated with decreased time to ovulation and increased ovulation rates at higher doses when compared with the traditional protocol. Abstract : For women with polycystic ovary syndrome, the stair-step clomiphene protocol is associated with decreased time to ovulation and increased ovulation rates at higher doses when compared with the traditional protocol.